Diabetic nephropathy with minimal change disease: a case report - Miao, Pengwei; Mo, Xiuting; Zhang, Xingkun; Zhang, Mianzhi (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) has become the main cause of end stage renal disease (ESRD) in the past decade. Diabetic kidney disease (DKD) is one of the most serious complications of diabetes. In clinical practice, the diagnosis of DKD is based primarily on clinical criteria, that is, patients almost do not undergo renal biopsy, leading to many non-diabetic kidney diseases (NDKDs) being misdiagnosed as DKD, thus increasing the incidence rate of DKD. The incidence of NDKD is also higher in those with DM. To date, few cases of minimal change disease (MCD) among those with DKD have been reported. Here, we report a case of diabetic nephropathy with pathological diagnosis, which was considered to be complicated with MCD according to the medical history, and was completely relieved after glucocorticoid treatment.Case descriptionA 49-year-old male patient with a diabetes duration of 3 years was admitted to our hospital mainly because of “bilateral lower extremity edema for 1 month”. The clinical manifestations were nephrotic syndrome and diabetic nephropathy, which were confirmed by renal biopsy. According to the medical history, DKD with MCD was considered. The patient received glucocorticoid for 6 months and was completely relieved of proteinuria.ConclusionRenal biopsy is helpful to differentiate diabetes with chronic kidney disease (CKD). DKD and DKD with MCD can be differentiated in the early stage of DKD but are difficult to differentiate in the late stage of DKD. In clinical practice, for such patients, we should also diagnose them carefully based on their medical history to reduce the misdiagnosis rate.